2008
DOI: 10.1007/s00339-008-4832-4
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion anisotropy and void development under cascade irradiation

Abstract: Cascade irradiation of metals gives rise to swelling as a result of the creation of voids and the evolution of the void ensemble. Under suitable circumstances, the originally disordered void distribution transforms into to a void lattice. As demonstrated previously, the understanding of the evolution and the unique features of the void ensemble requires a difference in the anisotropy of the diffusion (DAD) of vacancies and self-interstitial atoms (SIAs), which is achieved by one-dimensional diffusion of the SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…However, there are contradicting statements in the previous works about the mechanisms and dimensionality of di-interstitial SIA (di-SIA) and SIAC diffusion. 2,13,14,16,17 At the same time, the comparison with the recent experimental results showed a large discrepancy in the diffusivity of dislocation loops. 4 The understanding of the mechanisms of the production of large clusters of defects is of practical importance for reducing the irradiation embrittlement.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, there are contradicting statements in the previous works about the mechanisms and dimensionality of di-interstitial SIA (di-SIA) and SIAC diffusion. 2,13,14,16,17 At the same time, the comparison with the recent experimental results showed a large discrepancy in the diffusivity of dislocation loops. 4 The understanding of the mechanisms of the production of large clusters of defects is of practical importance for reducing the irradiation embrittlement.…”
Section: Introductionmentioning
confidence: 81%
“…The resulting data can be deployed as an input for the theoretical models of long time evolution of damaged material. 3,14,33,34 It was shown that both the SIAs and the vacancy loops have high one-dimensional (1D) mobility along close-packed crystal directions in bcc crystals. 10,31,32 The small clusters can switch their propagation direction between equivalent directions, which result in the three-dimensional (3D) diffusion at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first observation of a void lattice in irradiated materials [1], many theoretical models have been proposed to explain the formation of ordered microstructures [12][13][14][15][16][17]. One important family of the models is based on an elastic energy minimization argument [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the invariable presence of compositional disorder in the crystal lattice due to alloying and various thermal-mechanical treatment may lead to the trapping or scattering of the clusters [6,[33][34][35], drastically reducing the likelihood of long-range one-dimensional transport of interstitial defects. Moreover, recent investigations [36,37] showed that void lattice formation in ''pure" metals cannot occur if more than $1% of the interstitial atoms undergo one-dimensional diffusion. The development of large-scale heterogeneous void swelling found near grain boundaries and dislocation walls can also be understood without invoking the one-dimensional diffusion [38][39][40].…”
Section: Preliminary Considerationsmentioning
confidence: 99%